2003
DOI: 10.1097/00001199-200309000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Impairment, Activity, Participation, Life Satisfaction, and Survival in Persons With Locked-In Syndrome for Over a Decade

Abstract: Persons with initially stable locked-in syndrome can have prolonged survival, can live in the community if there is enough support, and have some measure of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
2
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 12 publications
6
98
2
3
Order By: Relevance
“…Doble et al 11 found that patients with locked-in syndrome, including people with an SCI experience an increase in communication with family and friends at 11 years related to technology use. 10 At least 52% of respondents increased the time they spent using the Internet after injury, and 76% of people with an SCI used the Internet for social entertainment in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Doble et al 11 found that patients with locked-in syndrome, including people with an SCI experience an increase in communication with family and friends at 11 years related to technology use. 10 At least 52% of respondents increased the time they spent using the Internet after injury, and 76% of people with an SCI used the Internet for social entertainment in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality is indeed high in acute LIS of vascular origin (87% within the first 4 months; Patterson and Grabois, 1986) and mean survival rate in ALS is 3-5 years with only a short period of time in LIS (Ludolph and Dengler, 1999). However, individuals in LIS may survive for long periods of time, sometimes exceeding 20 years (Doble et al, 2003;Leó n-Carrió n et al, 2002;Laureys et al, 2005). Doble et al (2003) reported a 10-year survival of 83% and 20-year survival of 40% in 29 stabilized (i.e., surviving more than 1 year) LIS patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals in LIS may survive for long periods of time, sometimes exceeding 20 years (Doble et al, 2003;Leó n-Carrió n et al, 2002;Laureys et al, 2005). Doble et al (2003) reported a 10-year survival of 83% and 20-year survival of 40% in 29 stabilized (i.e., surviving more than 1 year) LIS patients. Data from the French Association for Locked-In Syndrome (ALIS; www.alis-asso.fr) on 250 patients showed that mean time spent in LIS was 674 years (range 14 days-27 years; Laureys et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of better methods of communication, it is clear that, despite a high incidence of depression, most locked-in patients want antibiotics, want aggressive medical care, avoid "no-code" advanced directives, do not seek euthanasia, and want to stay alive (7). Some can return home provided there is sufficient support for their care.…”
mentioning
confidence: 99%